Allogenic controls on organic matter accumulation in the Woodford Shale in southern Oklahoma - Pew, Brayton Avery (Kansas State University, 2021)
The Woodford Shale is an organic-rich formation found in southern Oklahoma and Kansas and has been extensively studied due to recent advancements in hydrocarbon recovery in mudrock successions. The controls on organic matter formation and preservation within the Woodford are not entirely clear in southern Oklahoma, but previous work points towards upwelling and anoxic bottom-waters as leading factors for the high organic content. This study was performed on a Woodford Shale outcrop located along Interstate 35 (mile marker 44) in Carter County, Oklahoma and contains the middle and upper Woodford succession. The integration of facies and chemical analyses, including hand-held X-ray fluorescence (HHXRF), inductively-coupled plasma mass spectrometry (ICP-MS), X-ray diffraction (XRD) and total organic carbon (TOC), were performed to construct sedimentologic-chemostratigraphic logs that allowed the establishment of a stratigraphic framework and evaluation of depositional parameters such as detrital input, primary productivity, and degree of oxygenation during the accumulation of the studied succession. The I-35 Woodford Shale outcrop can be divided into three main sequences (1, 2, and 3, from base to top), with sequences 2 and 3 further subdivided into subsequences (A and B), based on changes in chemostratigraphic indices proxies for detrital input, primary productivity, and degree of oxygenation, and accompanied facies associations. Sequence 1 is characterized by distal, pelagic settling sediments with 12-13% TOC deposited under conditions of stable anoxia/euxinia, with low-moderate primary productivity. Sequence 2A is defined by interbedded pelagic and hemipelagic deposits with TOC between 7-11%. It was deposited in more oxic environments because of decreased water depths, resulting in less preservation of organics. The continued accumulation of pelagic and hemipelagic deposits in Sequence 2B is accompanied by increased primary productivity following an increase in nutrient supply from upwelling and continental waters, which resulted in organic contents of about 12%. The hemipelagic deposits of Sequence 3A display the highest TOC in the entire succession (14-20%), as a consequence of productivity boosts due to riverine nutrient input, despite the presence of overall oxic bottom waters with occasional anoxic events. Sequence 3B accumulated in a low to moderately productive environment under strongly anoxic conditions, resulting in the lowest TOC in the entire section (2-8%). The detailed study of the I-35 Woodford Shale outcrop indicates that high organic content (TOC>10%) is found in settings where primary productivity is high, regardless of the bottom-water conditions. Primary productivity was boosted by riverine nutrient input associated with shallowing waters. The results of this study suggest that organic flux is more important than anoxia in the burial of organics in the sediments, with anoxia oftentimes being a consequence of high organic flux.
Keywords: Woodford Shale